Solubility Characteristics and Microstructure of Bitumen: A Review - Han Liu; Haibo Ding; Yanjun Qiu; Hinrich Grothe (Buildings)
This is a comprehensive review of the significance of solubility theories, internal stability, and external compatibility within petroleum science and pavement engineering. The historical development and future trends of solubility methods in bitumen are discussed, emphasizing the importance of separating bitumen components based on solubility to establish a link with chemistry. The paper also highlights the development of solubility theories and various characterization tests for bitumen, as well as the distribution of functional groups of solvents and their parameters. Additionally, it explores the generation of solubility profiles for different types and aging states of bitumen based on solubility data and statistical correlation, and the use of stability diagrams to assess the internal stability of bitumen in different states. The potential for continued research in this field is emphasized to bridge the gap between fundamental chemistry and practical application, leading to improved formulations and enhanced performance of bitumen in various applications, ultimately resulting in more durable and stable pavement structures.